Food inflation, poverty, and urbanization - Headey, Derek D.; Hirvonen, Kalle (International Food Policy Research Institute, 2022)
After a long secular decline in the 20th century, food prices spiked sharply in 2007-08, 2010-11 and again in 2021-22. While often termed “food crises”, economists disagree on whether rising food prices increase or decrease poverty: poor people have high food expenditure shares but also produce and sell food, and higher food prices trigger food supply responses and growth in rural wages. One limitation of previous econometric studies is their focus on medium-run multi-year impacts, even though simulation analyses typically find negative impacts in the short run. In this study we therefore construct and analyze a novel short run panel of annual poverty and food price data for 33 middle income countries (MICs) over 2000-2019. Using standard panel data techniques, we find that increases in the real price of food predict reductions in $3.20/day poverty in less urbanized countries but increases in poverty in the most urbanized MICs.